Prognostic value of coronary artery calcium score in hospitalized COVID - 19 patients. (4th February 2022) - Motoc, A; Luchian, ML; Lochy, S; Belsack, D; Magne, J; Roosens, B; De Mey, J; Boeckstaens, S; Van Den Bussche, K; Geers, J; Galloo, X; Francois, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The association of known cardiovascular risk factors with poor prognosis of coronavirus disease 2019 (COVID-19) has been recently emphasized (1). Coronary artery calcium (CAC) score is considered a risk modifier in primary prevention of cardiovascular disease and has shown to improve cardiovascular risk prediction in addition to classical risk factors (2).  Purpose: We hypothesized that the absence of CAC might have an additional predictive value for an improved cardiovascular outcome of hospitalized COVID-19 patients. Methods: We prospectively included 310 consecutive hospitalized patients with COVID-19. Thirty patients with a history of coronary artery disease were excluded. Low dose non - contrast chest computed tomography (CT) was performed in all patients at admission. Visual assessment of CAC in every coronary artery was obtained by using an ordinal scoring of 0, 1, 2 or 3 corresponding to absent, mild, moderate or severe CAC score. A total score was calculated by summing the score of each vessel, which was further categorized as 0 (undetectable), 1-3 (mild), 4-5 (moderate) and ≥ 6 (severe). (Figure 1). Demographics, medical history, clinical characteristics, laboratory findings, imaging data, in-hospital treatment, and outcomes were retrospectively analyzed. A composite endpoint of major adverse cardiovascular events (MACE) was defined as all - cause mortality, heart failure, acute coronary syndrome, atrial fibrillation and stroke. Results: Two hundred eighty patients (63.2 ± 16.7 years old, 57.5% male) were included in the analysis. One hundred thirty one (46.7%) patients had a CAC score of 0. MACE rate was 21.8% (61 patients). Multivariable logistic regression showed that the absence of CAC was inversely associated with MACE (OR 0.209, 95% CI 0.052–0.833, p = 0.027), with a negative predictive value of 84.5% (sensitivity 72%, specificity 55%), independent of age, risk factors or disease severity (Figure 2). Conclusion: The absence of CAC had a high negative predictive value for MACE in patients hospitalized with COVID-19, independent of the presence of cardiac risk factors or disease severity. These findings reinforce the idea that the assessment of CAC could be a useful marker for risk stratification and management of COVID - 19 patients. Future directions should focus on the implementation of CAC score into mid - term and long - term follow - up of this particular population, to provide a more precise and earlier estimation of cardiovascular risk.